Does Rudeness Really Matter? The Effects of Rudeness on Task Performance and Helpfulness - Porath, Christine L.; Erez, Amir (Academy of Management Journal, 2007)
In three experimental studies, we provided an empirical test of how rudeness affects task performance and helpfulness. Different forms of rudeness—rudeness instigated by a direct authority figure, rudeness delivered by a third party, and imagined rudeness—converged to produce the same effects. Results from these studies showed that rudeness reduced performance on routine tasks as well as on creative tasks. We also found that rude behavior decreased helpfulness. We examined the processes that mediated the rudeness-performance relationship and found evidence that disruption to cognitive processes fully mediated that relationship.